151 Intake, Growth, and Insectifugal Outcomes Associated with Free-choice Supplementation of Garlic Products to Feedlot Steers. (8th October 2021) - Cheang-Deis, Iris Ho In; Lardner, Herbert; Rochon, Kateryn; Oyedeji, Oluwatobi; Block, Hushton; Asai-Coakwell, Mika; Erickson, Nathan; Durunna, Obioha N
Abstract: Conflicting anecdotal accounts from producers about their cattle performance and fly-repellence outcomes while receiving garlic-infused supplements have limited feeding decisions. This study evaluated differences in animal performance and insectifugal outcomes among four groups (26 steers per group) over two years (total = 208 steers). The steers either received non-garlic mineral supplement (MS), MS+0.3% garlic oil-based premix (GOil), MS+2.5% garlic powder (LGP), or MS+5% garlic powder (HGP). A completely randomized design was implemented where each steer was assigned to each treatment group while balancing for bodyweight and breed composition. Steers received a feedlot ration and free-choice mineral supplement for 86 and 108 d in the first and second year, respectively. Individual feed and supplement consumption were measured with automatic feeding units. Fly abundance on each animal was determined using digital images collected during weekly fly surveys. The ADG, feed efficiency, ultrasound body composition, and intake-related activities were also evaluated during the study. Data were analyzed using linear- or generalized linear mixed models in SAS. A significant year and Group×year interactions were observed for daily supplement intake (P < 0.02). Similar interactions (P < 0.04) were observed for feeding behaviors associated with supplement intake. Fly abundance during the peak months was below the economic threshold and was not different among the groups (P = 0.25), but the year and Group×year interactions were significant (P < 0.02). There were no differences among the groups for DMI (P = 0.81), ADG (P = 0.54) and gain to feed ratio (P = 0.34). The Group×year interactions were present for the change in ultrasound rib-fat-thickness. The reasons behind the differences in supplement intake are not clear but may be related to the garlic products' phytochemical profiles. These results suggest that further studies are required to identify the specific bioactive compounds in garlic that affect supplement intake.